Green bond premiums in the chinese secondary market - Karel Janda; Anna Kortusova; Binyi Zhang (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Green bonds have gained prominence in China's capital market as tools that help to fuel the transition to a climate-resilient economy. Although the issuance volume in the Chinese green bond market has been growing rapidly in recent years, the impact of the green label on bond pricing has not been adequately studied. Therefore, this paper investigates whether this newly developed financial instrument offers investors in China an attractive yield compared to other equivalent conventional bonds. By matching green bonds with their conventional counterparts and subsequently applying a fixed-effects estimation, our empirical results reveal a significant green bond yield premium of 1.8 basis points (bps) on average in the Chinese secondary market. In addition to that, we find that CBI certified green bond generate higher yields than self-labelled green bond in the Chinese market. Investors are found to be willing pay a higher price for green bonds issued by environmental, social and governance (ESG) performance-rated issuers. Our results point to some practical implications for investors and policymakers.
Keywords: G12; Q56; 330; Green Finance; Green bonds; ESG; China